2006
DOI: 10.2337/db05-1375
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for Advanced Glycation End Products Is Involved in Impaired Angiogenic Response in Diabetes

Abstract: Angiogenic response is impaired in diabetes. Here, we examined the involvement of receptor for advanced glycation end products (RAGE) in diabetes-related impairment of angiogenesis in vivo. Angiogenesis was determined in reconstituted basement membrane protein (matrigel) plugs containing vascular endothelial growth factor (VEGF) implanted into nondiabetic or insulin-deficient diabetic wild-type or RAGE ؊/؊ mice. The total, endothelial, and smooth muscle (or pericytes) cells in the matrigel were significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 48 publications
3
83
2
Order By: Relevance
“…Blockade of RAGE by administration of genetically engineered sRAGE successfully prevented the development of micro- 132,133 and macrovascular complications in diabetes [134][135][136] . We have also shown that adenoviral overexpression of esRAGE successfully restored the impaired angiogenic response in diabetic mice 101 . Sakaguchi et al found that administration of sRAGE markedly suppressed neointimal formation following arterial injury in non-diabetic mice 137 .…”
Section: F Circulating Srage and Esrage In Ckdmentioning
confidence: 86%
See 1 more Smart Citation
“…Blockade of RAGE by administration of genetically engineered sRAGE successfully prevented the development of micro- 132,133 and macrovascular complications in diabetes [134][135][136] . We have also shown that adenoviral overexpression of esRAGE successfully restored the impaired angiogenic response in diabetic mice 101 . Sakaguchi et al found that administration of sRAGE markedly suppressed neointimal formation following arterial injury in non-diabetic mice 137 .…”
Section: F Circulating Srage and Esrage In Ckdmentioning
confidence: 86%
“…esRAGE was found to be capable of neutralizing the effects of AGEs on endothelial cells in culture 12 . Adenoviral overexpression of esRAGE in vivo in mice reverses diabetic impairment of vascular dysfunction 101 . Thus, the decoy function of esRAGE may exhibit a feedback mechanism by which esRAGE prevents the activation of RAGE signaling.…”
Section: Endogenous Secretory Rage (Esrage)mentioning
confidence: 99%
“…However, diabetic patients have defects in the process of cicatrization and in the resolution of injury due to cellular dysfunction and inadequate production of proteases, cytokines and growth factors. The activation of receptors for advanced glycation end products may decrease angiogenesis and increase apoptosis (43). By contrast, the inflammatory reaction in diabetic lesions with poor cicatrization appears to slow recovery by generating an intense proteolytic response, which is mediated by elastase and neutrophils, TNF and IL-1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that RAGE is associated with plaque apoptosis and diabetic vascular responses 46,47) . In this study, we found that both temocaprilat and olmesartan prevented AGE-induced SMC apoptosis, probably due to the attenuation of RAGE/NADPH oxidase-dependent pathways.…”
Section: Discussionmentioning
confidence: 99%